Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Saat Pandemi Covid-19 (Perusahaaan Sub Sektor Restoran, Hotel & Pariwisata Yang Tercatat di BEI Tahun 2018-2022) - Rizki B, Anisa; Yudi, Yudi; Tiswiyanti, Wiwik (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This research aims to analyze the comparison of company financial performance before and during the COVID-19 pandemic in the restaurant, hotel and tourism sub-sectors listed on the Indonesia Stock Exchange (BEI) in 2018-2022. This research uses a quantitative descriptive method with purposive sampling technique. The sample used in this research consisted of 140 quarterly financial reports. Data analysis was carried out using descriptive statistics, normality tests, and paired t tests with the help of SPSS 26 software. The research results showed that the Return on Assets (ROA) and Gross Profit Margin (GPM) ratios did not experience significant changes before and during the pandemic. However, the Current Ratio, Quick Ratio, Debt to Equity Ratio, and Fixed Charge Coverage (FCC) ratios showed a significant decline during the pandemic, which had a negative impact on the company's financial performance.